Advanced detection and tracking in medium PRF radar - Hughes, Evan J.; Lewis, Michael B. (Cranfield University, 2009)
This paper describes an improved method of target tracking particularly applicable to littoral environments where a wide range of clutter characteristics are present. A light weight multiple hypothesis tracker based on multiple intelligent software agents is presented.
4th EMRS DTC Technical Conference – Edinburgh 2007